Get Rich or Die Tryin' : Perceived Earnings, Perceived Mortality Rate and the Value of a Statistical Life of Potential Work-Migrants from Nepal - Shrestha, Maheshwor (World Bank, Washington, DC, 2017)
Do potential migrants have accurate information about the risks and returns of migrating abroad? And, given the information they have, what is their revealed willingness to trade risks for higher earnings? To answer these questions, this paper sets up and analyzes a randomized field experiment among 3,319 potential work migrants from Nepal to Malaysia and the Persian Gulf countries. The experiment provides them with information on wages and mortality incidences in their choice destination, and tracks their migration decision three months later. The findings show that potential migrants severely overestimate their mortality rate abroad, and that information on mortality incidences lowers this expectation. Potential migrants without prior foreign migration experience also overestimate their earnings potential abroad, and information on earnings lowers this expectation. Using exogenous variation in expectations for the inexperienced potential migrants generated by the experiment, the study estimates migration elasticities of 0.7 in expected earnings and 0.5 in expected mortality. The experiment allows the calculation of the trade-off the inexperienced potential migrants make between earnings and mortality risk, and hence their value of a statistical life. The estimates range from US$0.28 million to US$0.54 million, which is a reasonable range for a poor population.